Role of Bolus Dose of Fentanyl (4μgm/kg) in Attenuating Presser Response of Laryngoscope and Tracheal Intubation (TAJ: Journal of Teachers Association, 2018)
Fentanyl is an opoid drug. It is effective in controlling pain during intra operative period. It was also observed thermodynamically state intra operatively. Hence it was planned to attenuating the hypertensive and tachycardiac response to laryngoscopey and trachel intubation by using bolus dose of Fentanyl (4μgm /kg).TAJ 2011; 24(2): 124-127